Prognostic roles of mitochondrial transcription termination factors in non-small cell lung cancer - Sun, Shuangyan (Oncol Lett, 2019)
Mitochondrial transcription termination factors (MTERFs) regulate mitochondrial gene transcription and metabolism in numerous types of cells. Previous studies have indicated that MTERFs serve pivotal roles in the pathogenesis of various cancer types. However, the expression and prognostic roles of MTERFs in patients with non-small cell lung cancer (NSCLC) remain elusive. The present study investigated the gene alteration frequency and expression level using Gene Expression Omnibus datasets and reverse transcription-quantitative polymerase chain reaction, and evaluated the prognostic roles of MTERFs in patients with NSCLC using the Kaplan-Meier plotter database. In human lung cancer tissues, it was observed that the mRNA levels of MTERF1, 2, 3 and 4 were positively associated with the copy number of these genes. The mRNA expression levels of MTERF1 and 3 were significantly increased in NSCLC tissues compared with adjacent non-tumor tissues; however, the mRNA expression of MTERF2 was significantly decreased in NSCLC tissues. High mRNA expression levels of MTERF1, 2, 3 and 4 were strongly associated with an improved overall survival rate (OS) in patients with lung adenocarcinoma. Additionally, high mRNA expression levels of MTERF1, 2, 3 and 4 were also strongly associated with an improved OS of patients with NSCLC in the earlier stages of disease (stage I) or patients with negative surgical margins. These results indicate the critical prognostic values of MTERF expression levels in NSCLC. The findings of the present study may be beneficial for understanding the molecular biology mechanism of NSCLC and for generating effective therapeutic approaches for patients with NSCLC.